ATRT-21. RHABDOID PREDISPOSITION SYNDROME: REPORT OF MOLECULAR PROFILES AND TREATMENT APPROACH IN THREE CHILDREN WITH SYNCHRONOUS ATYPICAL TERATOID/RHABDOID TUMOR AND MALIGNANT RHABDOID TUMOR. (4th December 2020) - Shatara, Margaret; Gupta, Ajay; Arja, Mohamed H Abu; Conley, Suzanne E; Patel, Priyal; Boué, Daniel R; Pierson, Christopher R; Thomas, Diana L; Meyer, Erin K; Shah, Summit H; Jones, Jeremy; Martin, Lisa; et al.
Abstract: BACKGROUND: Rhabdoid predisposition syndrome is characterized by germline alterations in SMARCB1 or SMARCA4, leading to synchronous or metachronous central nervous system (CNS) and extra-CNS rhabdoid tumors. Rare survivors have been reported to date. METHODS: We describe the molecular profiling and treatment regimen of three patients with synchronous atypical teratoid/rhabdoid tumor (ATRT) and malignant rhabdoid tumor of the kidney (MRT-K). All patients underwent radical nephrectomy of the kidney, and gross total resection of the primary CNS tumor was achieved for two patients. An intensive chemotherapy regimen was administered; an induction phase based on the modified Third Intergroup Rhabdomyosarcoma Study (IRS-III) for ATRT followed by a consolidation phase with three cycles of high-dose chemotherapy and autologous hematopoietic progenitor cell rescue, without irradiation. All three patients were enrolled on an institutional comprehensive genomic profiling protocol. RESULTS: A germline focal 22q deletion, including SMARCB1, was detected in two patients, while the third patient had a maternally-inherited heterozygous frameshift variant in SMARCB1 . Somatic loss of heterozygosity of 22q was identified in all patients, resulting in biallelic inactivation of SMARCB1 . Divergent tumor subgroups were described using DNA methylation. The three MRT-K samples were classified as MYC subtype. One ATRT was classified as SHH while the other as TYR. One patient is currently three years off-therapy without evidence of disease, while the other two patients have completed the consolidation phase without recurrent disease. CONCLUSION: Molecular profiling of CNS and extra-CNS rhabdoid tumors revealed different epigenetic subgroups. An intensive multimodal therapeutic approach without irradiation may achieve prolonged survival.